THE IMPLEMENTATION OF INPATIENT MEDICAL RECORD DOCUMENT STORAGE IN MANTUP PUBLIC HEALTH CENTER LAMONGAN REGENCY: A Review: TINJAUAN PELAKSANAAN PENYIMPANAN DOKUMEN REKAM MEDIS RAWAT INAP DI PUSKESMAS MANTUP KABUPATEN LAMONGAN - Ratna Frenty Nurkhalim (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2022)
Medical records documents must be managed properly so as not to be damaged or lost so that they can be reused for further treatment by implementing a storage system. A good storage system will facilitate storage, speed up retrieval, protect DRM from the dangers of theft, physical, chemical, and biological damage. The purpose of the study is to know the picture of the implementation of hospitalization DRM storage at Mantup Health Center lamongan regency.This type of research uses descriptive by way of observation and interview. A sample of 93 Inpatient medical records in the period 2020. The results of the study are storage systems using decentralization and the alignment of direct number systems. In its implementation still found Inpatient medical records stored outside the storage rack and retrieval has not used tracer. The accuracy of the alignment of 93 documents is 84 (90%) that are appropriate and 9 (10%) are not appropriate.This is due to the limited time and burden of the officer's personnel. Retention is done once a year. The conclusion of the study is that the implementation of DRM storage has policies and SPO related to storage. The alignment uses a direct numbers system and a decentralized storage system. Still found documents that are stored do not match the medical record number and some are stored off the shelf, it is expected that the leadership to monitor and evaluate the implementation of SPO, create color codes on maps, use tracers, create retention and extermination schedules, and the addition of storage shelves..